Unmatched case control study on risk factors of defaulter among newly diagnosed TB patients on DOTS registered under RNTCP in Hooghly district, West Bengal, India - Mallick, Arkajyoti; Haldar, Santanu; Sarkar, Soma; Kundu, Santanu; Sinha, Samik; Sadhukhan, Sanjoy K. (International Journal Of Community Medicine And Public Health, 2017)
Background: Tuberculosis is still a major public health problem in India and in addition to this, non-adherence to DOTS makes it more difficult to manage and increase risk of drug resistance. The objective was to study the factors associated with defaulter to DOTS among newly diagnosed TB patients treated under RNTCP registered in Hooghly district, West Bengal, India. Methods: A community based unmatched case control study was conducted with the help of predesigned pretested schedule among 99 defaulters and 103 non defaulters aged 15 years and above and registered between 1st April 2013 to 31st March 2014. Data was analyzed using SPSS software (version 20). Univariate analysis was done to find out the association of outcome with different variables under study. Variable with odd ratio 3 or more included in multivariate logistic regression model. Results: If patients were main earning member, smoker, lacking of perception regarding fatality of TB, having information source other than DOTS provider and sub center as treatment center, were found as significantly associated with defaulting in final multivariate regression model. Conclusions: An approach, towards modification of smoking behavior, adequate health education and information dissemination and qualitative improvement of treatment center including training of health staffs are essential for treatment adherence.